(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The reality of women’s lives remains invisible to men andwomen alike and this invisibility persist at all levels beginning with thefamily to the nation. The mere fact that“women hold up half the sky” does not appear to give them a position of dignityand equality. True, that over the yearswomen have made great strides to many areas with notable progress in reducingsome gender gaps. Yet “afflicted worldin which we live is characterized by deeply unequal sharing of the burden ofadversities between women and men”.